Whey Protein Lycosome Formulation Improves Vascular Functions and Plasma Lipids with Reduction of Markers of Inflammation and Oxidative Stress in Prehypertension. (24th December 2012) - Petyaev, Ivan M.; Dovgalevsky, Pavel Y.; Klochkov, Victor A.; Chalyk, Natalya E.; Kyle, Nigel
Abstract : Parameters reflecting cardiovascular health and inflammation were studied in a pilot clinical trial conducted on 40 patients with prehypertension. The patients were treated with a new proprietary formulation of a whey protein (WP) isolate embedded into lycopene micelles (WPL) during a 1-month period. Control groups received lycopene or WP as a singular formulation or placebo pills for the same period of time. Combined WPL formulation of whey protein and lycopene has caused multiple favorable changes in the cardiovascular function (including a tendency to the reduced systemic blood pressure), the plasma lipid profile, and the inflammatory status of patients with prehypertension, whereas singular formulations of the compounds and placebo did not have such an effect. The reduction of plasma triglycerides and cholesterol fractions and almost two-fold decline in C-reactive protein (CRP) and inflammatory oxidative damage (IOD) levels as well as an increase in nitric oxide (NO), tissue oxygenation (StO2 ), and flow-mediated dilation values constitute the most significant benefit/outcome of the treatment with the combined formulation of whey protein and lycopene. The treatment did not affect the values of ankle-brachial index (ABI), body weight, and body mass index (BMI).